Association between gender disadvantage factors and postnatal psychological distress among young women: A community-based study in rural India. Issue 7 (3rd July 2021) - Khanna, Tina; Garg, Priyanka; Akhtar, Faiyaz; Mehra, Sunil
ABSTRACT: Common mental health disorders are studied extensively among adult women globally. However, they remain under-researched among young women. This study aims to determine whether gender disadvantage factors are associated with psychological distress among young women in rural India, where the child sex ratio is lower than the national average. A cross-sectional survey was conducted in rural Pune, India. A total of 229 young married women who had a live birth in the last 12 months were screened for psychological distress. The predictors of psychological distress were estimated using multivariable logistic regression analyses. Psychological distress was found among 50 respondents (21.9%). Young women who were married before 18 years had 2.19 times higher odds of distress than women who were married after 18 years. Young women who gave birth to a female infant had 2.43 times higher odds of distress than those who gave birth to a male infant. Lack of partner support and experience of postnatal health complications were other predictors. Study findings ascertain the role of gender disadvantage factors in causing psychological distress. From a public health perspective, early identification and treatment of psychological distress, is imperative, along with addressing gender inequitable practices.